2012
DOI: 10.1103/physrevb.86.045422
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of surfactant-assisted growth of polar CaO(111) oxide film: The case of water-based surfactant

Abstract: Surfactant-assisted growth of polar CaO(111) oxide film in the presence of water-based surfactant is studied by first-principles calculations both from thermodynamic and kinetic point of view. We show that the water molecules not only supply a surfactant by depositing hydrogen on the surface throughout the growth process, but also supply oxygen atoms as an elemental constituent in the film growth with rather small energy barriers, i.e. water oxygen atoms are easily inserted in top surface layer of the growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(3) Allowing the growth of thin oxide films characterized by a polar termination, otherwise unstable because of the presence of a diverging electrostatic dipole [32,33]. (4) Extending the stability regime of epitaxy-stabilized metastable structures [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Allowing the growth of thin oxide films characterized by a polar termination, otherwise unstable because of the presence of a diverging electrostatic dipole [32,33]. (4) Extending the stability regime of epitaxy-stabilized metastable structures [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as it is clear that bulk oxides with polar surfaces must be charge compensated (at least on the macroscopic level) and growth on such a surface can propagate the polar discontinuity to another location (see, e.g. [23][24][25]), the nature of surface and interface screening can change dynamically and adapt based on the current reservoir of available charge either inside the heterostructures or near the surface from the ambient. The effects can be dramatic and lead to secondary phase formation: for example, Lazarov et al [26] observed the polarity-induced nucleation of metallic inclusions within an oxide film grown on MgO(1 1 1).…”
Section: Introductionmentioning
confidence: 99%
“…the redistribution of electronic defects [1-3, 41, 42], ionic defects [43][44][45][46], or both [4,5,47,48]) or external (e.g. the development of rough surfaces during growth [49], or the adsorption of compensating layers or foreign species, which can eliminate dynamic surface roughening [23][24][25]50]) to minimize the total electrostatic energy of the system. Regardless, much of the issues are similar, and the ability to manipulate the screening charges dynamically is of particular interest to all these communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation